IMPLIKASI PROGRAM KETAHANAN PANGAN DALAM MENINGKATKAN PRODUKSI DAN PENDAPATAN PETANI - Megawaty Hafidz (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2009)
This Research is a political eksistensi evaluated from aspect of Abstract : This Research have the character of the survey and executed in Countryside of Menteng of Subdistrict of Burau of Regency of Luwu North representing one of Group of[is Effort Development of Food Resilience specially paddy crop. intake Sampel as source of primary data done at random modestly that is take the sampel 10% from 375 farmer people or 37 sampel in concerned at Program of Development of Food Resilience of through direct interview by using questionnaire ( quisioner), while data sekunder obtained from related/relevant institution or office in this research. Result of research indicate that the Earnings usahatani obtained [by] as according to wide [of] farm which give the advantage to farmer of equal to Rp 4.199.334. Execution impact program the PKP can give the increase produce and farmer earnings